CONTENT MODULE «BASES OF DATA VISUALIZATION. INFOGRAPHICS» IN GOOGLE WORKSPACE FOR EDUCATION (Innovative professional education, 2022)
Module «Fundamentals of data visualization. Infographics» is aimed at developing the methodological competence of pedagogical workers in the aspect of mastering the basics of the theory of data visualization by means of online services and programs, preparation and creation of infographics.
Keywords: electronic educational resources, visualization, infographics, professional development, professional education